FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN DUKUNGAN KELUARGA TENTANG ASI EKSKLUSIF DENGAN PERTUMBUHAN BAYI UMUR 6 BULAN DI WILAYAH KERJA PUSKESMAS SUKARAMAI MEDAN TAHUN 2020 - HELENA FRANSYSCA (JURNAL ILMIAH KOHESI, 2020)
This research aims to find out the relationship of maternal knowledge and attitude as well as family support about exclusivebreast milk with the growth of 6-month-old babies in the working area of Sukaramai Medan health center. This type ofresearch is analytically descriptive with cross sectional studies with a population of 32 samples. The sampling techniqueused is total sampling as well as using a hypothesis with a chi-square test. There is a significant relationship of maternalknowledge with the growth of a 6-month-old baby, obtained X2atung greater than X2tabel (12,264> 9,488). There is asignificant relationship of maternal attitude with the growth of a 6-month-old baby, obtained X2tatung greater than X2tabel(15,596> 9,488). There is a significant relationship between family support and the growth of 6-month-old babies, obtainedby X2000 (29,112> 9,488). Conclusion there is a significant relationship of maternal knowledge and attitude as well as familysupport with the growth of 6-month-old babies in the working area of Sukaramai Medan health center.